GAMBARAN EFEK SAMPING OBAT ANTIHIPERTENSI DI INSTALASI RAWAT INAP RUMAH SAKIT UNS - Dhea Asyifa Nurmalika; Risma Sakti Pambudi; Reni Ariastuti (Jurnal Buana Farma, 2024)
Drugs provide beneficial effects, but can also cause detrimental effects. Drug side effects (ESO) are conditions that arise outside of the desired effects of treatment and are different for each person. The aim of this study was to determine the side effects of using antihypertensive drugs in hypertensive patients at the UNS Hospital inpatient unit. The research is descriptive in nature with primary data from medical records and MESO sheets of hypertensive patients. The research subjects were inpatient hypertension patients at UNS Hospital who met the inclusion and exclusion criteria. The data is then analyzed using the percentage of the results for each parameter. The research results showed that out of a total of 81 patients who used antihypertensive drugs, there were 32 patients (32%) who experienced ESO. Where 7 patients used single drugs and 25 patients used combination drugs. The most common ESO from single drug use was ramipril with dry cough (25%), shortness of breath (8%), dizziness (17%) and nausea and vomiting (8%). Meanwhile, ESO in combination drugs is amlodipine and ramipril with dry cough (15%), dizziness (20%) and shortness of breath (2%).